Innovative education and training in high power laser plasmas (PowerLaPs) for plasma physics, high power laser matter interactions and high energy density physics: experimental diagnostics and simulations. (2020) - Pasley, John; Andrianaki, Georgia; Baroutsos, Andreas; Batani, Dimitri; Benis, Emmanouil P.; Ciardi, Andrea; Cook, Donna; Dimitriou, Vasilios; Dromey, Brendan; Fitilis, Ioannis; Gatti, Giancarlo; Grigoriadis, Anastasios; et al.
Abstract : The second and final year of the Erasmus Plus programme 'Innovative Education and Training in high power laser plasmas', otherwise known as PowerLaPs, is described. The PowerLaPs programme employs an innovative paradigm in that it is a multi-centre programme, where teaching takes place in five separate institutes with a range of different aims and styles of delivery. The 'in-class' time is limited to 4 weeks a year, and the programme spans 2 years. PowerLaPs aims to train students from across Europe in theoretical, applied and laboratory skills relevant to the pursuit of research in laser plasma interaction physics and inertial confinement fusion. Lectures are intermingled with laboratory sessions and continuous assessment activities. The programme, which is led by workers from the Hellenic Mediterranean University and supported by co-workers from the Queen's University Belfast, the University of Bordeaux, the Czech Technical University in Prague, Ecole Polytechnique, the University of Ioannina, the University of Salamanca and the University of York, has just finished its second and final year. Six Learning Teaching Training activities have been held at the Queen's University Belfast, the University of Bordeaux, the Czech Technical University, the University of Salamanca and the Institute of Plasma Physics and Lasers of the Hellenic Mediterranean University. The last of these institutes hosted two 2-week-long Intensive Programmes, while the activities at the other four universities were each 5 days in length. In addition, a 'Multiplier Event' was held at the University of Ioannina, which will be briefly described. In this second year, the work has concentrated on training in both experimental diagnostics and simulation techniques appropriate to the study of plasma physics, high power laser matter interactions and high energy density physics. The nature of the programme will be described in detail, and some metrics relating to the activities carried out will be presented. In particular, this paper will focus on the overall assessment of the programme.